Multiscale Analysis of Extracellular Matrix Remodeling in the Failing Heart. Issue 1 (8th January 2021) - Perestrelo, Ana Rubina; Silva, Ana Catarina; Oliver-De La Cruz, Jorge; Martino, Fabiana; Horváth, Vladimír; Caluori, Guido; Polanský, Ondřej; Vinarský, Vladimír; Azzato, Giulia; de Marco, Giuseppe; Žampachová, Víta; Skládal, Petr; et al.
Abstract : Rationale: Cardiac ECM (extracellular matrix) comprises a dynamic molecular network providing structural support to heart tissue function. Understanding the impact of ECM remodeling on cardiac cells during heart failure (HF) is essential to prevent adverse ventricular remodeling and restore organ functionality in affected patients. Objectives: We aimed to (1) identify consistent modifications to cardiac ECM structure and mechanics that contribute to HF and (2) determine the underlying molecular mechanisms. Methods and Results: We first performed decellularization of human and murine ECM (decellularized ECM) and then analyzed the pathological changes occurring in decellularized ECM during HF by atomic force microscopy, 2-photon microscopy, high-resolution 3-dimensional image analysis, and computational fluid dynamics simulation. We then performed molecular and functional assays in patient-derived cardiac fibroblasts based on YAP (yes-associated protein)-transcriptional enhanced associate domain (TEAD) mechanosensing activity and collagen contraction assays. The analysis of HF decellularized ECM resulting from ischemic or dilated cardiomyopathy, as well as from mouse infarcted tissue, identified a common pattern of modifications in their 3-dimensional topography. As compared with healthy heart, HF ECM exhibited aligned, flat, and compact fiber bundles, with reduced elasticity and organizational complexity. At the molecular level, RNA sequencing of HF cardiac fibroblasts highlighted the overrepresentation of dysregulated genes involved in ECM organization, or being connected to TGFβ1 (transforming growth factor β1), interleukin-1, TNF-α, and BDNF signaling pathways. Functional tests performed on HF cardiac fibroblasts pointed at mechanosensor YAP as a key player in ECM remodeling in the diseased heart via transcriptional activation of focal adhesion assembly. Finally, in vitro experiments clarified pathological cardiac ECM prevents cell homing, thus providing further hints to identify a possible window of action for cell therapy in cardiac diseases. Conclusions: Our multiparametric approach has highlighted repercussions of ECM remodeling on cell homing, cardiac fibroblast activation, and focal adhesion protein expression via hyperactivated YAP signaling during HF. Abstract : Supplemental Digital Content is available in the text.